OSTEITIS CONDENSANS ILII: AN UNUSUAL CASE OF SEVERE BACK PAIN DURING PREGNANCY - Saleh, Raisa; Arshad, Ainan; Ayaz, Ahmed (Journal of Ayub Medical College Abbottabad, 2021)
Background: Lower back pain is a common complaint in pregnancy which often impacts quality of life. An uncommon aetiology of lower back pain is Osteitis Condensans Ilii (OCI), a condition characterized by a triangular area of sclerosis of ilium adjacent to the sacroiliac joint. It is thought to be associated with pregnancy, but also affects non-pregnant women and men. We discuss a case of a 23-year-old woman, who presented during the 8th month of her first pregnancy with debilitating pain in her lower back. Several differential diagnoses were explored, including autoimmune aetiologies and pregnancy associated osteoporosis, before OCI was diagnosed via an MRI. The patient was managed conservatively with intravenous analgesics and physiotherapy, after which her pain abated gradually. On her 3rd day of admission, the patient went into premature labour and gave birth to a healthy child via vaginal delivery. Her pain resolved completely within days of delivering her baby. Keywords: Pregnancy; Low Back Pain; Osteitis; Sacroiliac Joint